2013
DOI: 10.15376/biores.8.2.1718-1730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Steam and Heat Treatments on Extractives and Lignin in Sapwood and Heartwood of Turkey Oak (Quercus cerris L.) Wood

Abstract: Combined treatment with steam and heat was imposed on green Turkey oak (Quercus cerris L.) wood, both for sapwood and heartwood. Steaming was carried out in an autoclave at 100, 120, or 130 °C, and then a portion of the samples was heated in an oven for 2 h at 120 or 180 °C. Extraction with ethanol provided the greatest extractive contents in sapwood, and the extractive quantity decreased as the heating temperature was increased to 180 °C. In contrast, extraction with dichloromethane provided the greatest extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…It can be seen that the content of extractives soluble in hot water was increased after modifi cation regardless of the modifi cation temperature, while the content of extractives soluble in organic solvent and lignin was increased with the increase of the modifi cation temperature. Similar results were obtained for thermally modifi ed Norway spruce (Picea abies L.), Scots pine (Pinus sylvestris L.) and Radiata pine (Pinus radiate D.) (Boonstra and Tjeerdsma, 2006) and for Turkey oak (Quercus cerris L.) (Todaro et al, 2013). According to the research of Esteves and Pareira (2009), most extractives disappear or decompose during thermal modifi cation; however, new compounds are formed, which are isolated as a result of degradation of the compounds in the cell walls of the wood.…”
Section: Determination Of Contact Angle Of Waterborne Coating 23 Odsupporting
confidence: 76%
“…It can be seen that the content of extractives soluble in hot water was increased after modifi cation regardless of the modifi cation temperature, while the content of extractives soluble in organic solvent and lignin was increased with the increase of the modifi cation temperature. Similar results were obtained for thermally modifi ed Norway spruce (Picea abies L.), Scots pine (Pinus sylvestris L.) and Radiata pine (Pinus radiate D.) (Boonstra and Tjeerdsma, 2006) and for Turkey oak (Quercus cerris L.) (Todaro et al, 2013). According to the research of Esteves and Pareira (2009), most extractives disappear or decompose during thermal modifi cation; however, new compounds are formed, which are isolated as a result of degradation of the compounds in the cell walls of the wood.…”
Section: Determination Of Contact Angle Of Waterborne Coating 23 Odsupporting
confidence: 76%
“…Samples of modern oak and the museum wood were also extracted to remove any non-biopolymer materials contributing to the elemental composition. The sequential extraction procedure removed 59.7% of the mass of the conserved wood (Table 2), compared with c. 1% of the mass typically removed from modern, untreated oak by extraction with similar solvents 32,33 . Hence, PEG represented the largest proportion of the mass of the conserved wood sample.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the lignin content increased in the sapwood samples as com- pared with the control, but not in the heartwood samples, indicating the importance of steaming when wet wood is used. In a recent study, Todaro et al (2013) found contrasting results for Turkey oak wood, showing that an increase of lignin content in the heartwood after a high temperature treatment was associated with a previous steaming treatment on wet wood. However, Dashti et al (2012) highlighted the difference of lignin content between sapwood and heartwood in terms of their different permeability and diffusion coefficients in Quercus infectoria Olivier.…”
Section: Lignin Contentmentioning
confidence: 92%